The Kurikulum Kontekstual-Inklusif : Sebagai Inovasi dalam Menjawab Ketimpangan Sosial Ekonomi - Ufik Rohmatul Fitria; Syafi'i, Asrop; Anam, Khoirul (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2025)
Socio-economic disparities in education remain a critical issue, particularly for marginalized groups who are often excluded from access, participation, and meaningful learning experiences. This study aims to propose a contextual-inclusive curriculum model as an innovative approach to address such disparities. Using a Systematic Literature Review (SLR) approach, this research analyzes 30 national and international journal articles published in the last ten years that explore the interrelation between curriculum, social justice, and inclusive education. The findings reveal that curricula designed to recognize the socio-economic diversity of learners can significantly enhance student motivation, self-confidence, and active engagement in learning. However, in practice, inclusive curricula are often implemented symbolically, failing to address instructional design, learning strategies, or assessment systems. Therefore, policy intervention, teacher capacity building, and community engagement are necessary to ensure inclusive curricula are genuinely and transformatively implemented in schools. This study contributes to strengthening the paradigm of equitable and socially just education in the Indonesian context.